2010
DOI: 10.4269/ajtmh.2010.10-0180
|View full text |Cite
|
Sign up to set email alerts
|

Using Giant African Pouched Rats to Detect Tuberculosis in Human Sputum Samples: 2009 Findings

Abstract: Tuberculosis is a major public health problem in developing countries, 1 where sputum smear microscopy is the most common technique for diagnosing the disease. This method has limitations, the most serious being inaccuracy, when large numbers of sputum samples are analyzed.2 Hence, alternative diagnostic tools are badly needed. In recent years, researchers have explored the possibility of using trained giant African pouched rats ( Cricetomys gambianus ), to screen sputum samples rapidly and accurately. A recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 3 publications
3
43
1
Order By: Relevance
“…Nevertheless, still more than a quarter of the adults with smear-positive TB were missed by the DOTS clinics. Previous studies have shown that the TB case detection rate increases by over 40% in the general population when trained rats are used as an enhanced case-finding tool (6,7). In the present study, rats increased case detection by 33.7% in adults that is slightly lower than 40% reported previously.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Nevertheless, still more than a quarter of the adults with smear-positive TB were missed by the DOTS clinics. Previous studies have shown that the TB case detection rate increases by over 40% in the general population when trained rats are used as an enhanced case-finding tool (6,7). In the present study, rats increased case detection by 33.7% in adults that is slightly lower than 40% reported previously.…”
Section: Discussioncontrasting
confidence: 71%
“…Trained TB detection rats have been in use in Tanzania and Mozambique as an enhanced case-finding tool under research, after smear microscopy, whereby they have increased TB case detection by over 40% (6,7). In recent years the percent increase in TB detection due to the trained rats has slightly dropped from 40 to 35-37% annually, probably reflecting the improved quality of smear microscopy in the collaborating DOTS centers.…”
mentioning
confidence: 99%
“…The rats also identified as positive an additional 927 TB samples initially indicated as negative but found in second microscopy to contain the bacillus. The authors concluded that the use of pouched rats for TB detection in developing countries certainly warrants further research [54]. Mgode et al evaluated rats' ability to discriminate between clinical sputum containing other Mycobacteria spp.…”
Section: Cricetomys Rats: a Potential Diagnostic Systemmentioning
confidence: 99%
“…Giant African pouched rats (Cricetomys gambianus) have been trained to recognize the smell of Mtb-infected sputum [36]. When samples were exposed to ten different rats, 91% of Mtb smear-positive samples were detected [37]. Attempts to mimic the rats using electronic and chromatographic methods have so far been disappointing.…”
Section: Breath Testsmentioning
confidence: 99%